2015
DOI: 10.1155/2015/291987
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Translocation of GLUT4 Results in Insulin Resistance of Atrophic Soleus Muscle

Abstract: Whether or not the atrophic skeletal muscle induces insulin resistance and its mechanisms are not resolved now. The antigravity soleus muscle showed a progressive atrophy in 1-week, 2-week, and 4-week tail-suspended rats. Hyperinsulinemic-euglycemic clamp showed that the steady-state glucose infusion rate was lower in 4-week tail-suspended rats than that in the control rats. The glucose uptake rates under insulin- or contraction-stimulation were significantly decreased in 4-week unloaded soleus muscle. The key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 31 publications
1
28
0
Order By: Relevance
“…For instance, 10-day limb immobilization in rats led to a significant reduction in p-AMPK expression in red gastrocnemius muscle compared to the contralateral leg. (46,51) These incompatible results fit the contradictory role of AMPK in cell fate in skeletal muscles. (49) In humans, patients with critical myopathy showed decreased AMPK activity in skeletal muscles compared with healthy controls.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…For instance, 10-day limb immobilization in rats led to a significant reduction in p-AMPK expression in red gastrocnemius muscle compared to the contralateral leg. (46,51) These incompatible results fit the contradictory role of AMPK in cell fate in skeletal muscles. (49) In humans, patients with critical myopathy showed decreased AMPK activity in skeletal muscles compared with healthy controls.…”
Section: Discussionmentioning
confidence: 78%
“…However, unchanged or even a higher AMPK activity during muscle atrophy has also been reported. (46,51) These incompatible results fit the contradictory role of AMPK in cell fate in skeletal muscles. On one hand, high activity of AMPK induces membrane GLUT4 expression as well as mitochondrial biogenesis, benefiting muscle glucose metabolism and cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…Since the major manifestation of insulin resistance is a reduced stimulated glucose disposal by skeletal muscle, we focused our attention on the effects of the immobilization on glucose transport in unloaded soleus muscle of diabetic rats. It has been previously demonstrated that insulin‐ and contraction‐stimulated glucose uptake decreases in atrophic soleus muscle of tail‐suspended rats [31]. Insulin resistance in skeletal muscle was due to the attenuated expression level of the glucose transport GLUT4 with or without insulin‐stimulation, decreased GLUT4 activity or impaired GLUT4 translocation to sarcolemma [31].…”
Section: Resultsmentioning
confidence: 99%
“…It has been previously demonstrated that insulin‐ and contraction‐stimulated glucose uptake decreases in atrophic soleus muscle of tail‐suspended rats [31]. Insulin resistance in skeletal muscle was due to the attenuated expression level of the glucose transport GLUT4 with or without insulin‐stimulation, decreased GLUT4 activity or impaired GLUT4 translocation to sarcolemma [31]. Since the reduced GLUT4 content in immobilized muscle likely contributes to the deleterious impact on the altered glucose metabolism of diabetic animals [32], the gene expression of GLUT4 in the red soleus muscle was assessed by RT‐PCR analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Extracellular matrix remodeling can affect the extent of axonal growth during reinnervation because collagen fibers can be a barrier and delay the diffusion of nerve growth hormone (SCHIAFFINO, KUROSE, KAWAMATA et al, 2013). These physiological events reduce glucose uptake and metabolism, predisposing muscle fibers to atrophy and to peripheral insulin resistance (LO, RUSSELL, TAYLOR et al, 1970;CODERRE, MONFAR, CHEN et al, 1992;HENRIKSEN, RODNICK, MONDON et al, 1997;XU, SONG, ZHANG et al, 2015).…”
Section: Introductionmentioning
confidence: 99%